(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
song, folk dance and distinguishable painting style. Both West Bengal and Odisha are situated in Eastern India. Among these two states, modes and forms of cultural aspects are very much interrelated, and even similar in some cases. Most famous and common cultural aspect among these two states is Patachitra. Patachitra is a unique art-form, which is based on mythological folktales and started from immemorial time. Not only in West Bengal and Odisha, but it is prevalent also in the other parts of India, as well as outside of the country. To identify the similarities and dissimilarities between Bengal pata and Odisha pata, and also the differences of the lifestyle of patuas or chitrakar, two famous Patua villages have been selected as the study area, which are Naya from West Bengal and Raghurajpur from Odisha. Culture is a combination of art, music, literature, behaviour, belief, rituals etc of a specific area. Cultural heritage refers to the tangible and intangible attributes of a group of people belonging to a specific place, followed by generation to generation. To recognize how the components and forms of patachitra differ with the different physical and social attributes, a household survey was conducted in both the areas of interest. Some indicators have been selected to identify the similarities and dissimilarities between these two areas on different aspects of Patachitra. It can be concluded that, though after evaluation the locational, physical, social , cultural differences are there, but the essence of Patachitra has created a cultural bonding between these two areas.